Compression and permeability properties of multiaxial warp-knit preforms - Padaki, N. V. (2008)
Textile preform properties such as compression and permeability greatly influence the quality of the composite material and its performance, particularly those prepared by injection moulding techniques like resin transfer moulding (RTM). Directionally oriented warp-knit biaxial, triaxial and quadraxial glass fabrics have been studied for these preform properties. The preform compression properties were tested on the universal testing machine up to a maximum force of 250 N. The rate of test liquid flow through these preforms has been measured using the horizontalwicking test method. The permeability of these preforms has been analyzed based on the liquid flow-rate data. Fibre orientation and fibre volume fraction of the preforms are observed to be important factors influencing these preform properties.